2017
DOI: 10.1177/0002764216689124
|View full text |Cite
|
Sign up to set email alerts
|

Elementary School Children’s Political Knowledge

Abstract: This study looks at the question of which domain-specific concepts regarding politics children already understand and to what extent a naïve theory of politics can be postulated. It shows that even children in first grade have political knowledge that becomes increasingly differentiated throughout their time in elementary school. Fourth graders’ knowledge is more elaborate than that of first graders. The migrant background of children has a negative influence on political knowledge. No gender-specific differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…Where knowledge, political participation, gender and migration background are concerned, we can note the following recent research findings. Studies concerning school-level political knowledge have repeatedly shown that pupils with a migration background tend to know less than other pupils (Goll et al, 2010;Weisseno and Eck, 2012;Weißeno and Eck, 2013;Abs and Hahn-Laudenberg, 2017;Goetzmann, 2017;Hahn-Laudenberg, 2017;Landwehr, 2017). In the present study, we also expect this to be the case.…”
Section: The Current State Of Researchsupporting
confidence: 66%
See 1 more Smart Citation
“…Where knowledge, political participation, gender and migration background are concerned, we can note the following recent research findings. Studies concerning school-level political knowledge have repeatedly shown that pupils with a migration background tend to know less than other pupils (Goll et al, 2010;Weisseno and Eck, 2012;Weißeno and Eck, 2013;Abs and Hahn-Laudenberg, 2017;Goetzmann, 2017;Hahn-Laudenberg, 2017;Landwehr, 2017). In the present study, we also expect this to be the case.…”
Section: The Current State Of Researchsupporting
confidence: 66%
“…Where gender-specific differences are concerned, these may variously be explained via socialisation theory or via structural or biological approaches. Socialisation according to gender roles has been seen to disadvantage girls with respect to political knowledge (Vollmar, 2012; for an alternative view, see Goetzmann, 2017). More broadly, there is much to suggest that gender-specific disparities in the educational sphere are primarily the result of socialisation processes.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…I also control for each adolescents' parents' measure of the dependent variable, because exposure to the political culture of the household directly influences young people's political attitudes, including their political character (Jennings and Niemi, 1974); party ID and issue attitudes (Tedin, 1974); racial attitude, tolerance, and trust (Dalton, 1980(Dalton, , 1982; and even European Union identity (Quintelier et al, 2014). Importantly, these findings hold consistently across diverse country settings, such as the United Kingdom (Greenstein et al, 1974), Germany (Goetzmann, 2017), France (Lignier and Pagis, 2017), Japan (Kawata, 1987), Sweden (Westholm, 1999), Switzerland (Fitzgerald, 2011), and Belgium (Hooghe and Boonen, 2015). The socioeconomic traits of families, such as parental income, occupational prestige, and educational attainment, are also significant predictors of children's political characteristics (Glass et al, 1986).…”
Section: Control Variablesmentioning
confidence: 99%
“…However, the scattered evidence available on this topic suggests that this process is different for women. Whilst starting off from very similar levels of political knowledge as children (Torney-Purta et al 2001;Goetzmann 2017), 1 women's knowledge lags behind that of men once they reach adulthood (Hahn 1998;Jennings 1996;Jennings and Niemi 1974). In the context of the US, Jennings (1996: 248) shows that over time women gain less political knowledge than men, which substantially increases the awareness gap between adult women and men (see also Jennings and Niemi 1981: 280-81).…”
Section: Gender Gap In Political Knowledge and Adult Rolesmentioning
confidence: 99%